Massive Pulmonary Embolism Thrombolysis: Early Clinical Markers of Treatment Efficacy - Portnoy, Elie; Wadhwa, Vibhor; Barbosa, Mariana de Carvalho; Weiss, Clifford R.; Holly, Brian; Lessne, Mark L.; Hong, Kelvin; Tamrazi, Anobel (Journal of Clinical Interventional Radiology ISVIR, 2018)
The authors seek to evaluate hemodynamic parameters as potential clinical markers of real-time clinical improvement among patients with massive pulmonary embolism (PE) in correlation with post-thrombolytic pulmonary arterial pressure improvement and overall clinical outcome. Thirteen patients with submassive or massive PE were admitted to the interventional radiology service and treated with catheter-directed thrombolysis. Among the four patients who qualified as massive PE, systolic blood pressure (BP) and vasopressor dependence suggested meaningful trends toward clinical improvement, after only 26.4% of treatment course/dose. Hemodynamic parameters such as systolic BP and inotropic vasopressor dependence may be considered in future treatment protocols as early indicators of treatment response.
Keywords: pulmonary embolism; thrombolysis; pulmonary arterial pressure